Households’ Relocation Decision in Air Pollution Context of Cotonou - AVOCE VIAGANNOU, FANOUGBO (My University, 2020)
The purpose of this paper is to analyse the determinants of the decision to relocate households in the context of air pollution in Cotonou. The study used the database produced in 2010 by the “Centre for Studies, Training and Research in Development” of the University of Abomey-Calavi in Benin, as parting of an assessment of the health effects of air pollution in Cotonou. A logit model of relocation decision was estimated using a sample of 584 households. The results showed that monthly average income, health expenditure, health status and secondary and higher education levels positively influenced the household’s decision to relocate. Moreover, it appears necessary to reduce health expenditure whilst improving the health status of the population, without neglecting the improvement of income levels; as well as the strengthening of secondary and higher education. Thus, taking into account the effects of air pollution in policies is still relevant to achieve sustainable development.
Keywords: air pollution; households’ relocation decision; health expenditure; migration; sustainable development; Cotonou.